-6a+13=19

Simple and best practice solution for -6a+13=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6a+13=19 equation:


Simplifying
-6a + 13 = 19

Reorder the terms:
13 + -6a = 19

Solving
13 + -6a = 19

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -6a = 19 + -13

Combine like terms: 13 + -13 = 0
0 + -6a = 19 + -13
-6a = 19 + -13

Combine like terms: 19 + -13 = 6
-6a = 6

Divide each side by '-6'.
a = -1

Simplifying
a = -1

See similar equations:

| 2h^2+h+14=y | | 5a-5=9-2a | | 16-3m=-2 | | -100k+-30=-75-50k | | 6x+6x^2=12 | | (-7x^4y)(5x^2+9x^6y^3-3y^3)= | | -6=-7-n | | 33-y=20 | | 40+3x=(5x-10) | | .50x+.25(70)=37.5 | | x-(21)=9 | | -9k=126 | | 22+y=25 | | -7x^4y(5x^2+9x^6y^3-3y^3)= | | cos(2x)*cos(4x)= | | -9=126 | | 1.2-n+3.4=10 | | 2x-53=17 | | 2=t(28-4.9t) | | 0.25x+.05(6-x)=.10(-29) | | 3n-10=56 | | 3x^2+3y^2+18x-42y+162=0 | | 42=4x+6y | | (2x^3)+16=0 | | 4y-4+y+28=5+5y+25-3y | | 5(n-18)=10 | | p=10-4y+y^2 | | x^2-72x+100=0 | | 36x^3-15x^2+84x-35=0 | | 9x+12=5x+8 | | 2=t(20-4.9t) | | 6x+7=7x+6 |

Equations solver categories